Self-care differences in COVID-19 pandemic situation - Ni Putu Wulan Purnama Sari; Jintana Artsanthia (Jurnal Ners, 2022)
Introduction: Coronavirus Disease-2019 (COVID-19) pandemic has been happening for years now and no one can guarantee when this situation will end. The best thing that we can do in this new normal era is doing different self-care activity than what we usually do before the pandemic. This study aimed to analyze self-care differences before and after pandemic situation in the general population. Methods: This cross-sectional study involved 645 respondents living in five congested communities in Surabaya, Indonesia. Sample was enrolled by means of cluster random sampling. Variables on this study was self-care activities related to new normal activies among community. Valid and reliable questionnaire of self-care activities was used in data collection. Independent sample t test was used in data analysis. Results: Most respondents were female (54.6%) in their productive age (29.7 ± 11.5 y.o.), graduated (77.8%), private employee (35.5%), having no income (45.7%), and live with more than 3-5 family members at home (43.4%). Before pandemic, self-care was mostly sufficient (21.8 ± 5.9). After pandemic, self-care was improved greatly but still in sufficient level (28.5 ± 4.8). There was a significant self care difference before and after pandemic situation in the general population (p = 0.000). Conclusions: Self-care activities changes significantly after COVID-19 pandemic situation in the general population, but it was still in unoptimal level. Efforts to improve individual self-care in new normal era are needed to ensure this activity is implemented in its optimal level.